Pelatihan Pembelajaran PAI Berbasis Teks Naratif Keagamaan Untuk Meningkatkan Kemampuan Berbahasa Siswa Sekolah Dasar - Lalu Surya Jagat; Ni Wayan Sadiyani; Suci Handayani; Runi Fazalani (STKIP Subang, 2025)
This community service activity aimed to improve teachers’ competence in implementing Islamic Religious Education (IRE) learning based on religious narrative texts to enhance elementary school students’ language skills. The program was conducted at an elementary school in Bagu Village, Central Lombok Regency, involving IRE teachers and classroom teachers. A participatory and collaborative approach was applied through needs analysis, training, implementation assistance, and evaluation stages. The training activities included conceptual presentations on narrative-based IRE learning, practical sessions on lesson plan development, and teaching simulations. The results indicated an improvement in teachers’ understanding and skills in integrating religious values with students’ language abilities, particularly in reading comprehension, speaking, and simple writing. Classroom implementation showed increased student participation, confidence in expressing ideas, and better understanding of religious values through storytelling activities. Therefore, narrative-based IRE learning training proved to be an effective strategy for strengthening language literacy and improving IRE learning in elementary schools.